Terapi Pijat Mengurangi Kelelahan, Kecemasan dan Gangguan Tidur Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisis - Dian Retno Pratiwi; I Ketut Sudiana; Ika Yuni Widyawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine and review what types of massage therapy can reduce fatigue, anxiety, and sleep disturbances experienced by CRF patients undergoing HD. The method used is a systematic review using five databases, namely Scopus, ScienceDirect, Pubmed, CINAHL, and ProQuest, with publication limits from 2016 to 2021, in English, full-text articles. The keywords used are â€œmassage therapyâ€ AND â€œfatigueâ€ AND â€œAnxietyâ€ AND â€œsleep disorderâ€ OR â€œsleep qualityâ€ AND â€œChronic Kidney Diseaseâ€ AND â€œhemodialysis.â€â€ The results showed that of the ten articles reviewed, there were types of massage therapy, namely back massage, foot massage, hand massage, and combinations with aromatherapy oils which were known to be more effective in reducing fatigue scores and anxiety and improving sleep quality. This review concludes that massage therapy is an effective, efficient therapy with no side effects for HD patients. However, to do this therapy, it is recommended to take a massage course or training first. Keywords: Sleep Disorders, CRF, Hemodialysis, Anxiety, Fatigue, Massage Therapy